Avaliação do comportamento dos pontos fiduciais faciais durante o envelhecimento humano - Aquino, Cleiton Paiva (2017)
Facial aging is known as a complex process that varies the shape and texture of thefacial area. Variations in shape include variation in craniofacial structure, while texture variation includes skin coloration, appearance of facial lines and wrinkles. Shape and texture are both considered the most common forms of facial aging patterns. Fiducial points are control points on an object that define characteristic regions with properties of interest to the application. Thus, the objective of this work is to evaluate the behavior offacial fiducial points during human aging. An evaluation was performed in a statistical manner and through classification, through the characteristics vectors obtained throughfacial fiducial points. For the accomplishment of this work, we had a social motivation,that is the aid in the search for missing persons, and another one of technical character,that is the perfection of facial recognition systems. Among the results we can highlight the behavior of increase, reduction and stabilization among some fiducial points. With regard to classification, we obtained a result of 84.29 % of correct answers when we compared the class with people under 20 years old and the class with people between 20 and 39 years old from the black men’s groups